Prevalence of extraintestinal manifestations in Korean inflammatory bowel disease patients - Yang, Bo Ram (PLoS One, 2018)
BACKGROUND: The prevalence of inflammatory bowel disease (IBD) in South Korea is increasing. Although extraintestinal manifestations (EIMs) are an important factor in the clinical outcomes of IBD patients, EIMs have not yet been investigated in Korea. Thus, we conducted a cross-sectional study to assess the prevalence of EIMs in Korean IBD patients. METHODS: The 2014 claims data from the National Health Insurance System (NHIS) of Korea were used. IBD patients were identified by codes for Crohn disease (CD) and ulcerative colitis (UC) in the NHIS registration system for rare or intractable diseases. International Classification of Diseases, Tenth Edition codes were used to identify EIM cases. To estimate the prevalence of EIMs in the general population of Korea, we used national sample data. Standardized prevalence ratios (SPRs) were calculated to compare the prevalence rates of EIMs among IBD patients to those among the general population of Korea. RESULTS: A total of 13,925 CD patients and 29,356 UC patients were identified. CD and UC patients were different in terms of demographics and utilization of medication. Among the 17 EIMs investigated, pyoderma gangrenosum, osteomalacia, Sweet syndrome, and scleritis were observed in very few patients. The SPRs were greater than 1 for all EIMs. Aphthous stomatitis, rheumatoid arthritis, and osteoporosis were highly prevalent in both CD and UC patients, but the SPRs of the EIMs were not high. CONCLUSION: The study confirmed that EIMs are more prevalent among IBD patients than among the general population of Korea. The prevalence of EIMs in IBD patients suggests the need for greater attention and effort in clinical practice.